Preparation and pre-clinical evaluation of flagellin-adjuvanted NOM vaccine candidate formulated with Spike protein against SARS-CoV-2 in mouse model. (October 2022) - Farshidi, Narges; Ghaedi, Tayebeh; Hassaniazad, Mehdi; Eftekhar, Ebrahim; Gouklani, Hamed; Farshidi, Hossein; Asadi Karam, Mohammad Reza; Shahbazi, Behzad; Kalani, Mehdi; Ahmadi, Khadijeh
Abstract: From December 2019, the outbreak of severe acute respiratory syndrome coronavirus 2 ( SARS-CoV-2 ) was started as a cluster of pneumonia cases in Wuhan, Hubei Province, China. The disturbing statistics of SARS-CoV-2 promoted scientists to develop an effective vaccine against this infection. NOM protein is a multi-epitope protein that designed based on Nucleocapsid, ORF3a, and Membrane proteins of SARS-CoV-2 . Flagellin is a structural protein that binds to the Toll-like receptor 5 and can enhance the immune response to a particular antigen. In this study, NOM protein as vaccine candidate was linked to the carboxyl and amino terminals of flagellin adjuvant derived from Salmonella enterica subsp. enterica serovar Dublin. Then, informatics evaluations were performed for both NOM protein and NOM protein linked to flagellin (FNOM). The interaction between the NOM and FNOM proteins with the TLR5 were assessed using docking analysis. The FNOM protein, which compared to the NOM protein, had a more suitable 3D structure and a stronger interaction with TLR5, was selected for experimental study. The FNOM and Spike (S) proteins expressed and then purified by Ni-NTA column as vaccine candidates. For analysis of immune response, anti-FNOM and anti-S proteins total IgG and IFN-γ, TNF-α, IL-6, IL-10, IL-22 and IL-17 cytokines were evaluated after vaccination of mice with vaccine candidates. The results indicated that the specific antisera (Total IgG) raised in mice that received FNOM protein formulated with S protein were higher than mice that received FNOM and S proteins alone. Also, IFN-γ and TNF-α levels after the spleen cells stimulation were significantly increased in mice that received the FNOM protein formulated with S protein compared to other groups. Immunogenic evaluations showed that, the FNOM chimeric protein could simultaneously elicit humoral and cell-mediated immune responses. Finally, it could be concluded that the FNOM protein formulated with S protein could be considered as potential vaccine candidate for protection against SARS-CoV-2 in the near future. Highlights: 1.The development of a safe and effective vaccine could reduce the rate of SARS-CoV-2 infection. 2.The FNOM recombinant protein and Spike (S) protein expressed and then purified by Ni-NTA column as vaccine candidates. 3.The specific antisera (Total IgG) raised in mice that received FNOM protein formulated with S protein were higher than mice that received FNOM and S proteins alone. 4.IFN-γ and TNF-α levels after the spleen cells stimulation were significantly increased in mice that received the FNOM protein formulated with S protein compared to other groups. 5.The FNOM protein formulated with S protein could be considered as potential vaccine candidate against SARS-CoV-2 .